2020
DOI: 10.1111/poms.13131
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Pricing Model of Digital Music: Subscription, Ownership or Mixed?

Abstract: Traditionally, consumers purchase physical music (often in the form of CDs or cassettes) from local retailers. With the development of Internet technology, the market share of digital music has grown rapidly in recent years. Unlike physical music, digital music is provided by several emerging digital music providers through the Internet to consumers. Pricing models of digital music are also drastically different from those of physical music. In this study, we identify three common schemes for selling digital m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 48 publications
1
21
0
Order By: Relevance
“…The impacts of product digitalization on a firm's operations and marketing decisions have been studied in the literature (see, e.g., Li et al., 2020; Tan & Carrillo, 2017). Corollary 1 demonstrates that product digitalization in the context of channel decentralization has a profound impact on a firm's bundling decisions as well.…”
Section: Analysis Of Manufacturer's Bundling Decisionmentioning
confidence: 99%
See 1 more Smart Citation
“…The impacts of product digitalization on a firm's operations and marketing decisions have been studied in the literature (see, e.g., Li et al., 2020; Tan & Carrillo, 2017). Corollary 1 demonstrates that product digitalization in the context of channel decentralization has a profound impact on a firm's bundling decisions as well.…”
Section: Analysis Of Manufacturer's Bundling Decisionmentioning
confidence: 99%
“…Compared to physical goods, they possess unique features such as negligible marginal production/delivery cost, unlimited capacity, and high sunk cost (e.g., R&D cost). To understand the interplay between digital goods bundling and channel decentralization, we focus on the case of zero marginal production cost, following the tradition of the literature on digital goods (e.g., Li et al., 2020; Tan & Carrillo, 2017) and on product bundling (e.g., Bhargava, 2012). Our analysis reveals that channel decentralization is most likely to lead to manufacturer bundling when the marginal production cost is zero.…”
Section: Introductionmentioning
confidence: 99%
“…Some scholars used the empirical research method [13][14][15]; others used model research method to analyze the impact of positive cross-network externality on the competition of platform enterprises [16,17]. Li et al compared and analyzed three online music pricing strategies of ownership, subscription, and mixed pricing by optimizing the model, and the results showed that positive cross-network externalities and consumers' reserve price for music services had key influences on the pricing strategies of music platforms [18]. Scholars who study video media platform assume that advertising will cause interference to the audience and explore the impact of negative cross-network externality on platform pricing or advertising strategy [1,19,20].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Young people, especially students, have emerged as the primary consumers, and digital music has emerged as one of their preferred forms of consumer material [1,2]. When users want speci c music, they can easily search for it by entering information like title or artist, but when they do not have a clear query, that is, when they want the music system to give them music that meets their preferences without a clear goal, personalized music recommendation can be a better solution [3,4].…”
Section: Introductionmentioning
confidence: 99%